Capillary electrophoresis and isoelectric focusing in peptide and protein analysis1. Issue 2 (23rd December 2012) - Righetti, Pier Giorgio; Sebastiano, Roberto; Citterio, Attilio; Wu, Fang‐Xiang; Ressom, Habtom; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> CZE and CIEF of proteins have preceded, and accompanied, the birth of proteomics. Although they might not be fully exploited in massive proteomic analyses (especially those projects aiming at a deep discovery of possibly the entire proteome of a cell or subcellular organelles or biological fluids), it still has interesting features and advantages, especially with samples of limited heterogeneity and in the field of purity checking for recombinant DNA proteins meant for human consumption. The purpose of this tutorial paper is to guide the reader through the history of the field, then through the main steps of the process, from sample preparation to analysis of proteins and peptides, while commenting on the constraints and caveats of the technique. The tutorial ends with an outlook on the future, which might be dominated by microchip electrophoresis, especially for ultrafast analyses of protein samples in a sieving mode, in presence of either sieving liquid polymers or firm gels polymerized within the microchannels. To this purpose, commercial instrumentation is already available on the market. This tutorial is part of the International Proteomics Tutorial Programme (IPTP 13).